The Influence of a Vitrectomy on the Diurnal Intraocular Pressure - Yong Woo Lee; Joon Mo Kim; Seong Hee Shim; Da Yeong Kim; Jeong Hun Bae; Ki Ho Park (Journal of Ophthalmology)
Purpose. To evaluate the diurnal intraocular pressure (IOP) in eyes after vitrectomy compared to that of healthy eyes. Methods. Twenty-one patients who had undergone vitrectomy and 21 age- and gender-matched normal controls were enrolled during the same period. We measured the diurnal IOP every two hours between 9 a.m. and 11 p.m. in all patients who were admitted for cataract surgery. Patients with a history of eye surgery (not including vitrectomy) or use of a medication that is associated with IOP were excluded. The IOP and ocular parameters of patients were compared with the same patients’ fellow healthy eyes and with normal eyes of age- and gender-matched controls. Results. There were no significant differences between vitrectomized eyes and normal fellow eyes with regard to all IOP parameters including the maximum, minimum, and IOP fluctuation values. Diurnal fluctuation of IOP (or the difference between the maximum and minimum IOP) was larger in vitrectomized eyes than it was in age- and gender-matched control eyes. Conclusions. Vitrectomy did not markedly affect the IOP. Although there were no severe complications after vitrectomy, the IOP fluctuation was wider in vitrectomized eyes than it was in normal eyes.